Control of root‐knot nematodes using Waltheria indica producing 4‐quinolone alkaloids. Issue 8 (15th March 2019) - Jang, Ja Yeong; Le Dang, Quang; Choi, Gyung Ja; Park, Hae Woong; Kim, Jin‐Cheol
Abstract: BACKGROUND: Waltheria indica exhibited strong nematocidal activity against Meloidogyne incognita, a causal agent of root‐knot nematode disease. This study aimed to characterize the nematocidal metabolites and to evaluate the efficacy of the formulated extract of W. indica in the biological control of M. incognita under both pot and field conditions. RESULTS: Three 4‐quinolone alkaloids, 5′‐methoxywaltherione A, waltherione A and waltherione C, were isolated and characterized as nematocidal metabolites. 5′‐Methoxywaltherione A and waltherione A caused high mortality in juveniles of Meloidogyne arenaria, Meloidogyne hapla, M. incognita and Bursaphelenchus xylophilus, whereas waltherione C exhibited significant nematocidal activity against only root‐knot nematodes. In pot experiments, application of a wettable powder‐type formulation of the ethyl acetate extract of W. indica ( W. indica WP20) at 26.7, 53.4 and 106.8 mg a.i. kg −1 soil significantly reduced the formation of galls and egg masses on the roots of tomato plants in a dose‐dependent manner. In addition, application of 20 mg a.i. per plant W. indica WP20 effectively reduced gall formation on the roots of melon plants and population density of nematode in soil compared with untreated control under field conditions. CONCLUSION: W. indica can be used as an effective botanical nematicide in the eco‐friendly control of root‐knot nematode disease. © 2019 Society of Chemical Industry Abstract : Waltheria indica containing waltheriones as nematocidal metabolites effectively suppressed the development of root‐knot nematode diseases in pot and field experiments. The plant can be used as an effective botanical nematicide.